The complete chloroplast genome of Syzygium acuminatissimum - Feng Zeng; Yanwen Deng; Xiaozhou Liu; Xuanxi Zhu; Guangwen Tan (Mitochondrial DNA. Part B. Resources, 2021)
Syzygium acuminatissimum is a valuable hard wood species in southern China. In this study, we sequenced, assembled and annotated the complete chloroplast genome of S. acuminatissimum. The complete cp genome of S. acuminatissimum was 159,352 bp in length, with a total of 109 unique annotated genes, including 78 protein-coding genes, 27 tRNA genes and 4 rRNA genes. Phylogenetic analysis showed that S. acuminatissimum was closely related to its congener S. aromaticum.